Czy zasada niesprzeczności jest „najpewniejszym prawem myślenia i bytu”? - Żabski, Eugeniusz (Filozofia Nauki, 2004)
Various arguments for and against principles of non-contradictions: ontological and logical are presented in this article. Two non-classical sentential calculi, in which logical principles of non-contradictions are not effective, are presented too.